The multidimensional work motivation scale: Psychometric studies in Portugal and Brazil - Santos, Nuno Rebelo dos (2022)
Purpose The purpose of this study is to present validation evidence of a Portuguese version of the Multidimensional Work Motivation Scale, an instrument within the framework of the Self-Determination Theory, suitable for both Brazil and Portugal. Design/methodology/approach The current study demonstrates the suitability of this version in both Portugal (N = 999) and Brazil (N = 720). The authors applied confirmatory factor analyses (CFA) and tested the invariance between samples. Findings Results from CFA found the same structural dimensions as in the original study, invariant across both samples. Convergent and discriminant validity were shown through correlations between motivation subscales with affective commitment and emotional exhaustion. Originality/value Overall, the data provided strong evidence for the reliability and validity of the Portuguese version of the scale and reinforces the instrument as a cross-culturally valid measure of work motivation.